Crime fiction a very short introduction - Bradford, Richard 1957- (Oxford University Press, 2015)
Crime fiction has been one of the most popular genres since the 19th century, but has roots in works as varied as Sophocles, Herodotus, and Shakespeare. In this 'Very Short Introduction' Richard Bradford explores the history of the genre, by considering the various definitions of 'crime fiction' and looking at how it has developed over time. Discussing the popularity of crime fiction worldwide and its various styles; the role that gender plays within the genre; spy fiction, and legal dramas and thrillers; he explores how the crime novel was shaped by the work of British and American authors in the 18th and 19th centuries
Includes bibliographical references and index
Keywords: Detective and mystery stories / History and criticism; Crime in literature; Englisch; Kriminalroman; Einführung